RDNA-16. THE ROLE OF RAD52 IN GENOMIC INSTABILITY AND THERAPEUTIC RESISTANCE OF MALIGNANT GLIOMAS. (5th November 2018) - Aguilar-Morante, Diana; Juul Elbæk, Kirstine; Frias, Alex; Hamerlik, Petra
Abstract: Glioblastoma (GBM) is the deadliest and most common primary brain tumor with median survival rates of less than two years. GBM is defined by hallmarks such as uncontrolled cellular proliferation, diffuse infiltration, propensity for necrosis, robust angiogenesis, resistance to apoptosis and rampant genomic instability. Inter- and intra-tumoral heterogeneity, cellular plasticity and de-regulated signaling pathways are plausible causes of resistance to existent therapies in GBM. As current therapies offer only limited survival benefits, the identification and validation of new approaches in glioblastoma management is of highest importance. RAD52 is one of the key homologous recombination (HR) proteins. Rad52 binds to single strand DNA (ssDNA) and so plays a crucial role in most HR events as well as restart of collapsed replication forks in response to oncogene-induced replication stress. Our recent findings show significantly higher Rad52 mRNA levels in malignant gliomas compared to normal brain, where its levels negatively correlate with GBM patient survival. Experimental data show that the inhibition of RAD52 by 6-Hydroxy-DL-Dopa (6OH-Dopa) impairs GBM cell survival due to increase in replication-transcription collisions leading to accumulation of DNA damage. These preliminary findings support for first time a novel role of RAD52 in glioblastoma. We believe that Rad52 targeting may hold promise in future therapeutic intervention in GBM